"There Are No Known Benefits . . .": Considering the Risk/Benefit Ratio of Qualitative Research. (July 2016) - Opsal, Tara; Wolgemuth, Jennifer; Cross, Jennifer; Kaanta, Tanya; Dickmann, Ellyn; Colomer, Soria; Erdil-Moody, Zeynep
Institutional review boards (IRBs) are responsible for weighing the risks and benefits of research participation. Qualitative researchers note numerous instances where IRB ethical frameworks fail to align with the ethics of their research projects and point out that IRB understandings of the benefits and risks of research often differ from those of the participants they seek to protect. This qualitative cross-case research investigates participants' interview experiences in six qualitative studies that differed in their methods, subject of focus, and populations. Our findings indicate that contemporary IRBs' use of population "vulnerability" and topic "sensitivity" to assess project risk does not adequately determine the benefits, risks, or ethicality of research. We recommend that IRBs treat as real the evidence for benefits in qualitative research, recognize that sensitivity and vulnerability do not predict risk, and encourage researchers to attend to relationships in their projects.